Biblical Mandate for Ecological Stewardship - Alphonsa, P J (Asian Horizons, 2024)
The paper entitled “Biblical Mandate for Ecological Stewardship” seeks to explore the Biblical canon that implores the protection of the natural and physical world. The Bible, as the inspired Word of God, deals primarily with the relationship between God and mankind and the way to salvation and life eternal. However, the Bible also presents tenets that entreat the protection of the natural and physical world in a holistic manner. Relationships must be seen in terms of responsibilities as well as privileges. Once responsible relationships are fulfilled, a major part of our environmental crisis will be corrected efficiently. There are many references in the Bible to the wonder and importance of the biophysical world that we today generally refer to as the ‘environment.’ These references, although written centuries ago, retain their relevance and point to the heart of many current environmental concerns. Christians should not negate their responsibility towards caring for the environment but should hold themselves accountable as trusted stewards of God’s creation.